RM2 and DB15 analogues bearing [177Lu]Lu-DOTAGA via different linkers, as radiotherapeutics: a head-to-head comparative study - Panagiotis Kanellopoulos; Athanasios Bitzios; Ivan Zelepukin; Ekaterina Bezverkhniaia; Theodosia Maina; Berthold A. Nock; Vladimir Tolmachev; Anna Orlova (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Bombesin analogues are gaining popularity as GRPR-targeting theranostic agents aiming to provide molecular tools for a patient-tailored management. We previously reported on two series of DOTAGA-bearing GRPR-antagonists, based on either [NMe-Gly11]RM26 (DOTAGA-X-DPhe-Gln-Trp-Ala-Val-NMe-Gly-His-Sta-Leu-NH2) or on DB15 (DOTAGA-X-SAR; SAR: DPhe-Gln-Trp-Ala-Val-NMe-Gly-His-Leu-NHEt) motifs, which were preclinically screened after labelling with In-111. In the current study, we aimed to evaluate in vitro and in vivo the four best-performing agents, AU-RM26-M2 (X: PEG2-Pip; Pip: 4-amino-1-carboxymethyl-piperidine), AU-RM26-M4 (X: Arg-Arg-Pip), AU-SAR-M1 (X: AMA-DIG; AMA: p-amino methylaniline, DIG: diglycolate) and AU-SAR-M2 (Arg-AMA-DIG), this time labelled with the therapeutic radionuclide Lu-177. Results All four [177Lu]Lu-peptide radioligands displayed highly GRPR-mediated cellular uptake, showing the typical profile of radioantagonists, with the bulk of cell-associated radioactivity being membrane-bound. The analogues demonstrated good in vivo stability, which was however further improved by in situ stabilization induced by pretreatment of animals with Entresto as the source of the potent neprilysin (NEP)-inhibitor sacubitrilat. The biodistribution profile of the four radiopeptides was determined in prostate cancer PC-3 xenograft-bearing mice at 4 h and 23 h pi, after Entresto pre-treatment. All peptide radioligands had a rapid clearance from the background tissues, with the highest activity uptake found in the implanted tumours, the kidneys and to a lesser extent the GRPR-rich pancreas. The activity in the pancreas and, on a smaller scale, in the kidneys was washed out by 23 h pi, while being highly retained in the tumours. Among the tested analogues, [177Lu]Lu-AU-SAR-M1 displayed the overall most favourable properties, combining the lowest retention in the kidneys with high and prolonged activity accumulation in the tumours. As a result, [177Lu]Lu-AU-SAR-M1 provided the best area under the curve (AUC) ratio between tumour and kidneys (5.4), in comparison with [177Lu]Lu-AU-SAR-M2 (3.8), [177Lu]Lu-AU-RM26-M4 (3.4), and [177Lu]Lu-AU-RM26-M2 (1.1). Conclusions In conclusion, these results qualify [177Lu]Lu-AU-SAR-M1 as the candidate of choice for further evaluation in a dedicated preclinical radiotherapy study.